2011
DOI: 10.1063/1.3615797
|View full text |Cite
|
Sign up to set email alerts
|

Cross-plane thermal conductivity of a PbSnSe/PbSe superlattice material

Abstract: The cross-plane thermal conductivity of a PbSnSe/PbSe multi-period superlattice (SL) grown by molecular beam epitaxy is obtained from continuous wave photoluminescence (PL) measurements and finite element analysis (FEA). PL measurement and FEA for a structure consisting of a multiple quantum well light emitting layer on top of a PbSnSe/PbSe SL with three different periodicities of 2.4, 3.6, and 4.8 nm revealed a cross-plane lattice thermal conductivity of 0.8 W/mK. The 58% reduction relative to the 1.9 W/mK va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…18 In particular, the work by Jeffers et al 18 echoes our prediction that the significant reduction in the cross-plane thermal conductivity of SLs of periods shorter than 5 nm is the result of stronger scattering of phonons by interfaces. To the best of our knowledge, there are no reports of the FIG.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…18 In particular, the work by Jeffers et al 18 echoes our prediction that the significant reduction in the cross-plane thermal conductivity of SLs of periods shorter than 5 nm is the result of stronger scattering of phonons by interfaces. To the best of our knowledge, there are no reports of the FIG.…”
Section: Discussionsupporting
confidence: 55%
“…4,8,13,17 In particular, Slack 17 has suggested that materials prepared using techniques which produce glass-like hugely reduced lattice thermal conductivity j ph without significantly reducing the power factor PF ¼ S 2 r, should help enhance ZT. Experimental studies 10,18 have clearly indicated the role of strong interface scattering of phonons in generating large reduction in j ph for thin-period superlattice (SL) structures. However, no fullscale and accurate calculations of phonon scattering rates and conductivity for nanocomposites of different dimensionalities and different volume fractions have been carried out that assess the full extent of the role of phonons in the enhancement of ZT with a high degree of confidence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sample M212 at a heat sink temperature of 150 K and 2.6 W of absorbed power has a MQW lattice temperature of 184.6 K. Hot spot MQW lattice temperatures were then used as boundary conditions in finite element modeling (QuickField) to determine the total thermal conductivity of the SL material. As with prior work [11], a sample with binary PbSe (M141) having known total thermal conductivity of 4.8 W/mK at 150 K, extrapolated from the data of Shalyt et al [13], was used to fit the Gaussian shaped pump laser spot size. A good fit was obtained with a beam spot FWHM of 530 μm, which agrees well with knife-edge measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 summarizes the three samples where the thicknesses of layers within each sample are calculated from total measured IV-VI layer thickness and shutter open times, which were as short as 3.6 sec, during MBE growth. PL measurements and cross-plane lattice thermal conductivity determination were performed according to procedures described previously [11]. Instead of maintaining the copper heat sink temperature with a thermoelectric cooling module, as done earlier, we used a liquid nitrogen cryostat with infrared transparent windows for diode laser (875 nm InGaAs diode pump laser) illumination and mid-IR PL light collection.…”
Section: Methodsmentioning
confidence: 99%
“…Made available by state‐of‐the art heteroepitaxy , SL consist of alternating thin layers of different materials stacked periodically. Most prominent applications of TE SL are Bi2Te3/Sb2Te3 , Si/Ge and SL based on PbTe and PbSe . Other SL based on Bi/Sb () or skutterudites () showed negligible or only small enhancements of the TE efficiency.…”
Section: Introductionmentioning
confidence: 99%